KRISIS POLITIK INDONESIA TAHUN 1965: ANALISIS SEJARAH DAN IMPLIKASINYA TERHADAP STABILITAS NASIONAL - Sinta Prahastini; Bahri Bahri (Prabayaksa: Journal of History Education, 2026)
The 1965 Indonesian political crisis marked a major turning point in the country's political development, profoundly reshaping its governance and national stability. This study aims to analyze the causes, dynamics, and implications of the 1965 political crisis for Indonesia's national stability. The study employed the historical method, consisting of heuristics, source criticism, interpretation, and historiography. Primary sources included government archives, official state documents, presidential speeches, and the Supersemar document, while secondary sources comprised scholarly books, journal articles, and previous studies on the 1965 political crisis. The findings indicate that the crisis resulted from the interaction of political rivalry among competing elites, ideological polarization, economic deterioration, and Cold War geopolitical dynamics. The 30 September Movement represented the culmination of these tensions and accelerated the transition of power from the Old Order to the New Order. The crisis subsequently transformed Indonesia's political system through political restructuring, the expansion of military influence, and the institutionalization of national stability as the primary governance paradigm. At the same time, it generated enduring consequences, including restrictions on democratic participation, collective social trauma, and unresolved challenges to reconciliation. Overall, the 1965 political crisis was a multidimensional historical event that fundamentally shaped Indonesia's political trajectory and remains significant for understanding the relationship between political stability, democracy, and historical reconciliation.